2020
DOI: 10.1111/ajt.15860
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the alloimmune basis and prognostic significance of Borderline T cell–mediated rejection

Abstract: Prognostic biomarkers of T cell–mediated rejection (TCMR) have not been adequately studied in the modern era. We evaluated 803 renal transplant recipients and correlated HLA‐DR/DQ molecular mismatch alloimmune risk categories (low, intermediate, high) with the severity, frequency, and persistence of TCMR. Allograft survival was reduced in recipients with Banff Borderline (hazard ratio [HR] 2.4, P = .003) and Banff ≥ IA TCMR (HR 4.3, P < .0001) including a subset who never developed de novo donor‐specific antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 58 publications
6
45
1
Order By: Relevance
“…We did not have sufficient histologic data to fully evaluate T cell–mediated rejection in this cohort. However, Wiebe et al found the same molecular mismatch categories used in this study significantly correlated with Banff borderline, Banff ≥IA, and Banff ≥IB T cell–mediated rejection free survival, providing further evidence for their alloimmune basis 15 . Additionally, the number of recurrent T cell–mediated rejections increased significantly with each grade of risk category.…”
Section: Discussionsupporting
confidence: 69%
“…We did not have sufficient histologic data to fully evaluate T cell–mediated rejection in this cohort. However, Wiebe et al found the same molecular mismatch categories used in this study significantly correlated with Banff borderline, Banff ≥IA, and Banff ≥IB T cell–mediated rejection free survival, providing further evidence for their alloimmune basis 15 . Additionally, the number of recurrent T cell–mediated rejections increased significantly with each grade of risk category.…”
Section: Discussionsupporting
confidence: 69%
“…One exception is a recent evaluation of isolated tubulitis, which did not support the utility of treatment and similar survival to those without tubulitis, 34 and in this study, we explicitly considered this separately as well. A recent report by Wiebe et al, affirms that borderline‐grade rejection is associated with a more than 2‐fold increased hazard for graft failure, and established that HLA DR/DQ mismatch with the donor kidney is important in its pathogenesis 35 . Treatment of Banff borderline changes may be considered as similar to Banff 1A, but are not typically reported in any detail.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the appearance of Human Leukocyte Antigen (HLA) DR/DQ DSA, which associates with worse graft survival, 26,34 frequently accompanied Borderline TCMR 22 . Together with evidence that Borderline TCMR correlates with the degree of HLA DR/DQ molecular mismatch, is linked to subsequent Banff ≥IA TCMR and/or DSA development, and is associated with allograft loss, 34,35 the aggregate evidence supports including Borderline TCMR in a conservative definition of BPAR.…”
Section: Discussionmentioning
confidence: 97%
“…In the CNI withdrawal RCTs, Borderline TCMR was included in the DSMB’s decision to halt the trials—the DSMB conservatively considered Borderline TCMR after an immune quiescent biopsy to represent loss of control of the primary alloimmune response 22,23 . Moreover, the appearance of Human Leukocyte Antigen (HLA) DR/DQ DSA, which associates with worse graft survival, 26,34 frequently accompanied Borderline TCMR 22 . Together with evidence that Borderline TCMR correlates with the degree of HLA DR/DQ molecular mismatch, is linked to subsequent Banff ≥IA TCMR and/or DSA development, and is associated with allograft loss, 34,35 the aggregate evidence supports including Borderline TCMR in a conservative definition of BPAR.…”
Section: Discussionmentioning
confidence: 99%